Small bowel motility in functional chronic constipation - Seidl, H.; Gundling, F.; Pehl, C.; Pfeiffer, A.; Schepp, W.; Schmidt, T. (Neurogastroenterology and motility, 2009)
In functional constipation, three pathophysiological subgroups have been identified: slow‐transit constipation (STC); normal‐transit constipation (NTC) and outlet delay (OD). Extracolonic manifestations, especially disturbed small bowel motility, are well known to occur in STC, but have rarely been studied in NTC and OD. To perform 24‐h‐ambulatory jejunal manometry in a large prospective series of clinical patients with chronic constipation of all subtypes. A total of 61 consecutive patients, referred to our tertiary gastroenterologic centre for chronic constipation (48 female, 13 male; mean age 57 (range 20–87) years), underwent jejunal 24‐h‐ambulatory manometry (standardized meal) after a transit‐time study (radio‐opaque markers), anorectal manometry, defecography and colonoscopy. Computerized and visual analysis by two independent observers was compared with the normal range of manometric variables, defined by data previously obtained in 50 healthy subjects (Gut 1996;38:859). Five patients were excluded from the study because of coexistence of OD and STC. No patient with OD (n = 8), but all patients with STC (n = 32) and 94% of patients with NTC (n = 16) showed small bowel motor abnormalities; both in postprandial response and fasting motility. The abnormal findings ranged from severe disturbances with complete loss of MMC to subtle changes of contraction parameters that could only be assessed by computerized analysis. No significant differences between STC‐ and NTC‐patients were found. Most findings pointed to an underlying enteric neuropathy. Intestinal prolonged‐ambulatory manometry adds valuable information to the pathophysiologic understanding of functional chronic constipation of STC‐ and NTC‐type, however there are no distinct manometric features to differentiate between both.